Beyond gated politics : reflections for the possibility of democracy - Coles, Romand, 1959- (University of Minnesota Press, 2005)
Beyond Gated Politics argues that the survival of democracy depends on recognizing the failings of disengaged liberal democracy and experimenting with more radical modes of democratic theory and action. Romand Coles moves beyond the paradigms of political liberalism, deliberative democracy, and communitarian republicanism, cultivating modes of public discourse that reflect and sustain the creative tension at the heart of democratic life and responsibility.